Dinamisasi Kajian Fikih: Sebuah Konsep Pendekatan Kontekstualisasi Fikih Sebagai Pemecah Problematika Hukum Islam - Mahmudi, Muhammad Aly; Masyhadi, Ahmad; Kholish, Fuad Nur (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2023)
The process of gradation about jurisprudence as islamic law seems to be stagnant and stops at the work of classical scholars who are sacred even this sacredness exceeds that of the nash of the original source texts of the Quran and Hadith in terms of the finished legal products presented. This understanding must be immediately broken so that the fiqh itself is not static so that it is dynamic because the understanding of the madhzhab of fiqh itself is dynamic, but this is not understood because the fanaticism of the madhhab is too deep. This article tries to explain the study of jurisprudence with a set of applications so that jurisprudence continues to exist as a solution to the problems of Islamic law, not hindering the development of Islam which is confused with classical social conditions. Using library research methods and quality research methods as normative legal research in this study concluded; first: The solution of the problem of reviving a time-sensitive jurisprudence; Second: The offer of a study of the dynamism of classical Jurisprudence by sticking to manhaj is not a mere product in the matter of jurisprudence. Keywords: Jurisprudence, Dynamic, Islamic Law